The Polish Investigation into Core Crimes Committed in Ukraine: Practical Aspects of the Functioning of the JIT (Polish Yearbook of International Law, 2024)
This article explains the legal basis and reasons for establishing a Joint Investigation Team by the Polish Prosecutor’s Office, investigating crimes committed as a result of the Russian aggression against Ukraine. It analyses the reasons why this investigation is so highly demanding and describes how it requires an unconventional approach to work from investigators, as well as enormous coordination efforts and support from the EU organs. Other states are involved in the JIT on an unprecedented scale, as well as the OTP ICC, and unconventional support has been offered by the EU organs, especially in the area of digitalisation of the exchange of evidence. The article highlights the state and picture of investigations conducted into crimes committed in Ukraine, both in domestic jurisdictions and before the ICC, as well as possibly before an international or internationalised tribunal established to adjudicate the crime of aggression. It explains how the Polish investigation – conducted within the framework of a JIT – has become an important element of ‘strategic litigation networks’ for serious international crimes.